Faktor- Faktor Yang Berhubungan Dengan Kecemasan Antenatal Pada Ibu Hamil Di Masa Pandemi Covid 19 Di UPTD Puskesmas Kalibaru Bekasi - Isfia Aunillah Rahma Soleha, (2021)
Pregnancy is a conception process that occurs when a sperm is fertilized an egg. During pregnancy women experience physiological, psychological, social, and hormonal changes. "Absence of support causes ambivalent feelings is an emotional attitude toward a person concerning an attitude, feelings, and anxiety during pregnancy called antenatal dismay - the feeling of anxiety, anxiety, and uncertainty about her pregnancy and the process that follows. The causes of anxiety for women include age, education, working status, monthly income of a husband, parity, pregnancy age, abortus history, birth history, etc. The beginning of the Covid 19 pandemic causes increased maternal anxiety. The study aims to learn the correlation of factors to the levels of antenatal anxiety in pregnant mothers during the Covid pandemic 19. There are a number of 63 respondents using sectional method of research, purposive sampling. Data processing with Google forms of coping mechanisms, joint support questionnaires, and pregnancy related anxiety revised-2 (praq-r2) tests of validity and retention. Research results in a significant link between the working status (p-valeu 0.037), the husband's monthly income (p-valeu 0.032), and the coping mechanisms (p-value 0.005) to the antenatal concerns of the pregnant mother during the Covid pandemic 19. A particularly influential factor in the antenatal anxiety of the pregnant mother at the time of hind Covid 19 - the work status, the husband's monthly income, and coping mechanisms.